Bioactive Methoxyflavones from Kaempferia parviflora Induce Apoptosis in Breast Cancer Cell Line - Supawadee Watcharin; Namuangruk Prathep; Sorawit Karnchanatat; Rittidech Tanomtong; Jittima Mahayothee; Piriyapongsa Srisuwan (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2025)
Kaempferia parviflora is commonly known as Black Ginger. It is a traditional Thai herbal plant rich in methoxyflavones and other bioactive compounds with promising anticancer properties. Breast cancer remains a leading cause of mortality worldwide, and current therapies face challenges such as toxicity and drug resistance. This study aims to evaluate the cytotoxic effects of ethanol extract of Kaempferia parviflora on human breast cancer cell lines (MCF-7 and MDA-MB-231) and to identify the main bioactive compounds responsible for its anticancer activity. Rhizomes were collected from Central Thailand, extracted using 70% ethanol via maceration, and concentrated with rotary evaporation. Breast cancer cells were cultured and treated with varying extract concentrations for 24 to 72 hours. Cytotoxicity was assessed using the MTT assay, and active compounds were quantified via HPLC. Results show a dose-dependent decrease in cell viability, with IC50 values ranging from 60 to 85 μg/mL. Apoptosis induction was confirmed by fluorescence microscopy and increased caspase-3 activity (up to 4.1-fold). HPLC analysis revealed significant concentrations of 5,7-dimethoxyflavone and 3,5,7-trimethoxyflavone, suggesting their role in ROS-mediated apoptosis. Future research should focus on detailed molecular mechanisms, in vivo toxicity and efficacy, and clinical translation. This study supports Kaempferia parviflora as a potential natural adjuvant in breast cancer therapy.